Predictors of Mobile Video Gaming on Musculoskeletal Pain among University Students in Selangor, Malaysia - Phuah, Jireh, Rong Yao; Viswanath, Sundar; Vinodhkumar, Ramalingam (Bahiana Journals, 2021)
| INTRODUCTION: Mobile video gaming among university students has increased rapidly, more than before the COVID-19 pandemic. This is very concerning as this could spark various problems, such as musculoskeletal pain and gaming disorders. OBJECTIVES: The present study is to identify the predictors of mobile video gaming on musculoskeletal pain among university students in Selangor, Malaysia. PARTICIPANTS AND METHODS: This study was conducted online using a self-reported online questionnaire via Google Form and sent to university students in Selangor, Malaysia. Participants' gaming addiction was measured using the Ten Item Internet Gaming Disorder Test (IGDT-10) questionnaire, and the prevalence of musculoskeletal pain was assessed by the Modified Nordic Musculoskeletal Questionnaire (MNMQ). The data was analyzed using SPSS version 25. A descriptive and binomial linear regression test was used to predict the variables. The statistical significance was set at p < 0.05, and odds ratios were calculated with confidence intervals of 95%. RESULTS: The prevalence of Internet Gaming Disorder among university students in Selangor, Malaysia is 1.8% (n=3). The neck region (74.2%) was the most commonly reported body region with musculoskeletal pain, followed by the shoulder region (60.7 %), lower back region (55.8 %), and upper back region (50.9 %). The body position was the only predictor of mobile video gaming with musculoskeletal pain (p = 0.002) in the lower back region. CONCLUSION: According to the findings of this study, the prevalence of Internet Gaming Disorder (IGD) among university students was low and not addicted to gaming in the Covid-19 lockdown. We also found that participants who sat while playing mobile video games were more likely to develop low back pain. However, one of the limiting factors could be prolonged sitting in virtual classes during the lockdown, which causes low back pain.